2017
DOI: 10.2217/nmt-2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

Light, Sleep and Circadian Rhythms in Older Adults With Alzheimer’s Disease and Related Dementias

Abstract: Alzheimer's disease and related dementias (ADRD) can cause sleep and behavioral problems that are problematic for ADRD patients and their family caregivers. Light therapy has shown promise as a nonpharmacological treatment, and preliminary studies demonstrate that timed light exposure can consolidate and improve nighttime sleep efficiency, increase daytime wakefulness and reduce evening agitation without the adverse effects of pharmacological solutions. Compliance with light treatment and the accurate measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 84 publications
2
48
0
Order By: Relevance
“…However, another randomized controlled trial of 48 patients (mean age 83.4years) in two nursing homes in the UK with diagnosed dementia, sleep disruption, and agitated behavior did not find similar cognitive benefit of bright light (99). The discrepancy may be attributed to differences in treatment dose, such as exposure duration and intensity of light, that are especially important for the elderly who have reduced responses of the circadian system to light exposure (100); future studies should examine these possibilities.…”
Section: Circadian Interventionsmentioning
confidence: 98%
“…However, another randomized controlled trial of 48 patients (mean age 83.4years) in two nursing homes in the UK with diagnosed dementia, sleep disruption, and agitated behavior did not find similar cognitive benefit of bright light (99). The discrepancy may be attributed to differences in treatment dose, such as exposure duration and intensity of light, that are especially important for the elderly who have reduced responses of the circadian system to light exposure (100); future studies should examine these possibilities.…”
Section: Circadian Interventionsmentioning
confidence: 98%
“…Disrupted environmental factors, such as light exposure, social cues, activity, and mealtimes, influence the period, phase, and amplitude of circadian rhythms. Without sufficient exposure to timed light, the biological clock becomes desynchronized with the solar day, resulting in deleterious effects on various physiological functions, neurobehavioral performance, and sleep [78]. Older adults and, to a greater extent, those institutionalized are more likely to be exposed to less robust daytime light [79].…”
Section: Sleep and Depressionmentioning
confidence: 99%
“…Improvements in sleep, depression, and reduced agitation were the primary indicators for the effectiveness of using bright light therapy for people living with dementia. All five reviews (Scales, Zimmerman, & Miller, 2018;Figueiro, 2017 to have a stronger effect on women compared to men living with dementia. Scales et al (2018) found that bright light therapy can reduce agitation and depression.…”
Section: Bright Light Therapymentioning
confidence: 99%
“…Useful suggestions include: making use of natural light as much as possible (Figueiro, 2017;Scales et al 2018); providing darkness at night and light during the daytime (Figueiro, 2017;Hanford & Figueiro, 2013); and removing constant dim lighting commonly found in care homes (Hanford & Figueiro, 2013 (Anderson et al 2011). A small-scale study by Bauer et al (2015) found no significant changes in wandering and restlessness when using Snoezelen compared with 'common practice'.…”
Section: Bright Light Therapymentioning
confidence: 99%